Bracketing phenogenotypic limits of mammalian hybridization - Yoland Savriama; Mia Valtonen; Juhana I. Kammonen; Pasi Rastas; Olli-Pekka Smolander; Annina Lyyski; Teemu J. Häkkinen; Ian J. Corfe; Sylvain Gerber; Isaac Salazar-Ciudad; Lars Paulin; Liisa Holm; et al. (Royal Society Open Science, 2018)
An increasing number of mammalian species have been shown to have a history of hybridization and introgression based on genetic analyses. Only relatively few fossils, however, preserve genetic material, and morphology must be used to identify the species and determine whether morphologically intermediate fossils could represent hybrids. Because dental and cranial fossils are typically the key body parts studied in mammalian palaeontology, here we bracket the potential for phenotypically extreme hybridizations by examining uniquely preserved cranio-dental material of a captive hybrid between grey and ringed seals. We analysed how distinct these species are genetically and morphologically, how easy it is to identify the hybrids using morphology and whether comparable hybridizations happen in the wild. We show that the genetic distance between these species is more than twice the modern human–Neanderthal distance, but still within that of morphologically similar species pairs known to hybridize. By contrast, morphological and developmental analyses show grey and ringed seals to be highly disparate, and that the hybrid is a predictable intermediate. Genetic analyses of the parent populations reveal introgression in the wild, suggesting that grey–ringed seal hybridization is not limited to captivity. Taken together, we postulate that there is considerable potential for mammalian hybridization between phenotypically disparate taxa.